Direito de resistência: mitigador de riscos - Martin, Beatriz (2022)
The right of resistance has always been seen as a legal instrument for the defense of men, more specifically for the defense of individual rights. Within this perspective, Thomas Hobbes presents a fundamental philosophical paradigm: the celebration of a social contract is necessary to stabilize human relations and structure a safe environment, more conducive to human development. His perspective of preserving life, as an individual phenomenon, is the starting point of this work. Understanding the hobbesian philosophy is essential to absorb all the elements consistent whit post-modernity and that deserve to be restructured in accordance with current demands. Hobbes shows himself in conformity with the parameters demanded by post-modernity. Although it requires changes and complements, since the author wrote in a period of intellectual transition from the Middle Ages to the Modern Age and couldn’t foresse or understand the social changes caused by post-modernity. Using Hobbes’ philosophy as the foundation of the right of resistance, one must understand its changes throughout history, analyzing its legal and positive aspects, accepted today. The right of resistance has always been studied as a way of defending individual rights in the face of abuses committed by the State, which should have minimal intervention in the lifes of citizens. However, the emergence of the Welfare State, aimed at second-generation human rights that demand state action for their implementation, made the right of resistance a much more complex legal institute. Delimiting the limits of action of the State, companies and people has become a herculean task within a society that can no longer be considered class society, according to the marxist standards of the 19th century. The increase in complexity and contingency provided by scientific advances triggered a new paradigm of sociological study: risk society. If Karl Marx undestood all nuances of nineteenth-century society, classifying it as a class society, Ulrich Beck was able to improve his view, adding to economic study the evolution of natural sciences and all the implications caused in people’s lives. Although it isn’t the only way of analyze post-modernity, the risk perspective is very suitable for structuring the magnitude of the challenge that lies ahead: the preservation of the human species and planet Earth. Understanding that the civilizational risks provided by industrial/technological advances put the existance of everything and everyone at risk means realizing that it is necessary to mitigate them. Some authors propose that the realization of a natural contract, in the same tone as Hobbes’ social contract, capable of controlling scientific advances and limiting its scope of action, respecting nature in all its strenght. Other scholars notice the tendency of defend a society of control, capable of extirpating individual freedoms and dominating all aspects of citizens’ lives, “minimizing risks”. Post-modern society needs a tool that is capable of making human beings understand the responsability of their actions and respect both the neighbor and the planet wich we live in. Within this frame work, the right of resistance proves to be an effective tool, as it allows immediate action to protect the Earth and the human species, opening up the possibility of later analysis of legal responsabilities. The right of resistance oriented towards post-modern values, facing a perspective of equivalence between people and nature, is capable of mitigating post-industrial risks